Staggered boards, corporate opacity and firm value - Duru, Augustine; Wang, Dechun; Zhao, Yijiang (Journal of Banking & Finance, 2013)
We explore the effect of corporate opacity on the relation between staggered boards and firm value. We find that through mitigating takeover pressure, staggered boards become increasingly beneficial to firm value as opacity increases. In addition, we document that staggered boards reduce value only in transparent firms. Additional tests indicate that, as opacity increases, staggered boards bear an increasingly positive relation to research and development and CEO pay-performance sensitivity. Taken together, these results suggest that corporate opacity affects the value impact of takeover protection.